1808. Matrix-Assisted Laser Desorption/Ionization-Time of Flight (MALDI-TOF) and Vitek 2 Along With Antimicrobial Stewardship (ASP) Result in Faster Antimicrobial Therapy for Infected Patients: The CHI Health Experience. (26th November 2018) - Cavalieri, Stephen; Kwon, Seunghyug; Vivekanandan, Renuga; Ased, Sumaya; Carroll, Cassara; Schmidt, David; Destache, Christopher
Abstract: Background: Rapid organism identification (ID) and antimicrobial susceptibility testing (AST) are critical to treatment of infected patients. We sought to capture time between specimens collected for bacterial culture and appropriate therapy for patients, along with other pertinent patient management data from 2017 (without MALDI-TOF/Vitek 2 and ASP) and 2018 (with MALDI-TOF/Vitek 2 and ASP). Methods: Patients were eligible if admitted to CHI Health in March or April 2018 either with positive sputum, blood, or urine culture. Patients were retrospectively obtained from the Microbiology Laboratory for March 2017 and sequential patients with positive culture were reviewed. A total of 75 patients from each year (25 positive blood cultures, 25 urine cultures, 25 sputum cultures), , respectively, were compared. A time-in-motion study was performed to compare time to identification (ID), AST results and acted upon by ASP. Data were entered into SPSS (ver. 25) for analysis. Results are reported as mean (±SD) or percentage. Results: Mean patient age and Charlson comorbidity index was not significantly different between 2017 and 2018. Time to obtain culture, delivery to Microbiology, and Gram-stain was not different between the two groups. Time to organism ID was significantly faster in 2018 (2018, 25.2 ± 13.7; 2017, 34.2 ± 17 hours, P = 0.001). Time to AST results was also significantly faster for patients in 2018 compared with 2017 (19.8 ± 14.1 compared with 28.5 ± 15.1 hours, P = 0.001). ASP recommended significantly more adjustments to empiric antimicrobial therapy (25% of 2018 vs. 1% in 2017, P < 0.001). In addition, length of hospital stay was significantly shorter for patients in 2018 compared with 2017 (2018, 8.3 ± 7 days; 2017, 15.6 ± 18.3 days, P < 0.001). Finally, in-hospital length of antimicrobial therapy was significantly shorter in 2018 compared with 2017 (2018, 6.6 ± 3.7 days; 2017, 8.8 ± 7.7 days, P < 0.05). Conclusion: The use of MALDI-TOF/Vitek 2 leads to an average 18 hours faster microbial ID and AST results. ASP is able to make recommendations for infectious diseases management more appropriately with quicker ID and AST results. Disclosures: All authors: No reported disclosures.